Environmental and Socio-Economic Impacts of Crude Palm Oil and Kernel Production - Dian Kristina; Feri Afrinaldi; Nilda Tri Putri (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
Palm oil had become one of Indonesia’s leading commodities, contributing significantly to national economic development; however, it faced sustainability challenges, particularly concerning greenhouse gas (GHG) emissions in line with international standards. This study examined the measurement of environmental impact per monetary unit of Crude Palm Oil (CPO) and kernel production in Palm Oil Mill X, by integrating environmental and socio-economic impacts through Eco-efficiency Analysis. The environmental impact assessment was conducted using the Life Cycle Assessment (LCA) method, while the socio-economic impact values were measured using the Economic Input-Output (EIO) method. The data used in this study consisted of primary data and secondary data. Primary data were collected directly from Palm Oil Mill X, including information on production volumes, energy consumption and waste generation. Secondary data were obtained from published literature, government reports and national statistical database to complement and validate the primary data used in the analysis. The study evaluated eleven environmental impact categories, one of which was GWP. The research findings indicated that for a functional unit of 1 ton of CPO, the GWP was measured at 556.31 kg CO₂ eq/ton CPO, with approximately 80% of the GWP originating from CPO processing and wastewater (POME). In terms of socio-economic aspects, the wage multiplier was recorded at 0.930 and the tax contribution at 0.0698, demonstrating the significant contribution of the palm oil industry to labor income. The final economic contribution value (G⁺) was noted to be Rp 23,728,407/ton CPO. The results of the Eco-efficiency Analysis revealed that the GWP per Rupiah was 2.34 × 10⁻⁵ kg CO₂ eq/Rp, indicating opportunities for emission reduction through the use of cleaner energy. This study provided a quantitative overview of the interrelationship between environmental performance and socio-economic benefits, serving as a strategic reference for enhancing the sustainability of the palm oil industry.